Respuesta :
The answer is: "Step 3" .
_____________________________________________________
Note: "Step 3" incorrectly shows: "−6m + 6m = −48 − 12n + 4n " .
______________________________________________________
{Rather than the correct equation; which is:
" - 6m + 6m = - 48 – 12n + 4 + 4n " .}.
___________________________________________________
Note of interest:
___________________________________________________
Although not asked in the question/problem, let us continue with the correct equation; & to solve for" n ;
" - 6m + 6m = - 48 – 12n + (4 + 4n) ;
→ " 0 = - 48 – 12n + 4 + 4n " ;
__________________________
Combine the "like terms" on the "right hand side of the equation:
___________________________
-48 + 4 = -44 ;
- 12n + 4n = - 8n ;
__________________________
→ Rewrite the equation: " 0 = -8n – 44 " ;
↔ " - 8n – 44 = 0 " ;
Add "44" to each side of the equation;
→ -8n – 44 + 44 = 0 + 44 ;
to get:
→ -8n = 44 ;
Now, divide EACH SIDE of the equation by: "-8 " ;
to isolate "n" on one side of the equation; & to solve for "n" ;
→ -8n / 8 = 44 / 8 ;
→ n = 44/8 = (44 ÷ 4) / (8÷4) = 11/2 ;
n = "[tex] \frac{11}{2} [/tex]" ; or, write as: "5 [tex] \frac{1}{2} [/tex]" ;
or, write as: " 5.5 " .
______________________________________________________
_____________________________________________________
Note: "Step 3" incorrectly shows: "−6m + 6m = −48 − 12n + 4n " .
______________________________________________________
{Rather than the correct equation; which is:
" - 6m + 6m = - 48 – 12n + 4 + 4n " .}.
___________________________________________________
Note of interest:
___________________________________________________
Although not asked in the question/problem, let us continue with the correct equation; & to solve for" n ;
" - 6m + 6m = - 48 – 12n + (4 + 4n) ;
→ " 0 = - 48 – 12n + 4 + 4n " ;
__________________________
Combine the "like terms" on the "right hand side of the equation:
___________________________
-48 + 4 = -44 ;
- 12n + 4n = - 8n ;
__________________________
→ Rewrite the equation: " 0 = -8n – 44 " ;
↔ " - 8n – 44 = 0 " ;
Add "44" to each side of the equation;
→ -8n – 44 + 44 = 0 + 44 ;
to get:
→ -8n = 44 ;
Now, divide EACH SIDE of the equation by: "-8 " ;
to isolate "n" on one side of the equation; & to solve for "n" ;
→ -8n / 8 = 44 / 8 ;
→ n = 44/8 = (44 ÷ 4) / (8÷4) = 11/2 ;
n = "[tex] \frac{11}{2} [/tex]" ; or, write as: "5 [tex] \frac{1}{2} [/tex]" ;
or, write as: " 5.5 " .
______________________________________________________